Intimate partner and family abuse: a casebook of gender inclusive-therapy - Hamel, John (Springer, 2008)
Beyond ideology: alternative therapies for domestic violence / John Hamel -- An ounce of prevention: stopping violence before it begins / Derek Ball and William J. Hiebert -- After the fall: using the needs ABC model with couples affected domestic violence / Tom Caplan -- Examining women's rage in intimate partner violence / Kimberly Flemke -- The Souzas: using problem-centered systems therapy with IPV / Alison Heru -- Mary & Mark: couples therapy with a female batterer and her husband / Michael Mesmer -- Vivian 'Rae' Bailey: reciprocal family violence with a female batterer / Laura Dreuth Zeman -- Treating a family in crisis: the Christiansons / Ellen L. Bowen -- Who's holding the baby? Infant-led systems work in IPV / Wendy Bunston -- The moveable genogram: family intervention techniques towards breaking cycles of intergenerational conflict / Karen Cohen -- Co-parenting counseling with high-conflict parents in the presence of domestic violence / K. Kerstin Gutierrez -- Multi-modal treatment: the Wyman family / Catherine Lieb -- Subject to change: elder abuse in an East Indian family / Melissa C. Anderson -- Use of the medicine wheel and other experiential approaches in domestic violence and anger management therapy / Lori Bloom -- Therapeutic interventions to domestic violence with immigrant couples / Mirna E. Carranza -- Unresolved family violence: the Samaras / Jodi Klugman-Rabb -- Who started it? Circular dynamics in family violence / Darlene Pratt -- I learned to think for myself: a solution-focused approach to domestic violence therapy / Martin Söderquist & Bo Gunnehill -- Supervision and family safety: working with domestic violence / Arlene Vetere and Jan Cooper